The use of music-based activities to foster stress and rhythm in virtual EFL learning - Jiménez Varela, Nicolás 1996-; Ellis Rodríguez, Abraham Ricardo 1997-; Pacheco Salas, Lorely 1996-; Moya Mora, Yoselyn 1994-; Zumbado Venegas, Álvaro 1969- ([Alajuela, Costa Rica], 2023)
In Costa Rican EFL classrooms, music has always been part of the learning process. Even when students enter kindergarten, they are in contact with music, which is used as a didactic tool. In this project, we examine the use of music-based activities to foster stress and rhythm in second language learning (L2) in virtual settings. We took into consideration music-based activities and English learning, and the possibility of these two being interconnected by rhythm and stress. This inquiry followed an exploratory-sequential design to, first, search for opinions, thoughts, and skills developed on a small sample and then, to determine whether the findings could be observed in a similar group. The students that formed the sample took part in oral interviews and music-based activities where data was collected from ninth-grade students at Bilingual Highschool of Palmares and the Bilingual Highschool of Grecia. In the quantitative phase, a pre and posttest was applied to measure the changes that the students had after carrying out musical activities, where stress and rhythm were taken into account; in the qualitative part, oral interviews and surveys were developed. Data showed that using music-based activities helps foster stress and rhythm in L2 in virtual learning settings. Through this study, we aimed to make a significant contribution for teachers and students implementing new learning methodologies where music might help learners improve their vocabulary, listening, and pronunciation skills while developing stress and rhythm in their L2 process. On the last chapter conclusions, limitations, and recommendations were offered. In regards of limitations, the most relevant are the fact that there is a scarce amount of local research, and the points of view addressed were just the students´. Then concerning the recommendations.
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede de Occidente, 2023
Keywords: INGLÉS -- ESTUDIO Y ENSEÑANZA; INGLES -- ENSEÑANZA SECUNDARIA -- METODOLOGIA; MUSICA EN LA EDUCACION; INGLÉS -- ESTUDIO Y ENSEÑANZA -- HABLANTES EXTRANJEROS; APRENDIZAJE -- METODOLOGIA